2006
DOI: 10.1002/pmic.200500770
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of liver tissues subjected to early ischemia/reperfusion injury during human orthotopic liver transplantation

Abstract: Knowledge of early molecular events occurring upon ischemia/reperfusion (I/R) during liver transplantation (LT) is of great importance to improve the therapeutic intervention of surgical treatment. However, nowadays, few data are available on early protein targets of I/R injury. To identify these proteins, we used a differential proteomics approach in the characterization human liver biopsies during I/R upon LT. Analyses were performed on nine donor livers during LT. By using 2-DE and MALDI-TOF MS, we identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 38 publications
2
56
0
Order By: Relevance
“…Recent reports show that a few proteins are altered in humans undergoing liver transplantation. 25,44,45 In addition, some other proteins were also altered in rabbit hearts following I/R injury. 24,46 However, these studies were conducted using whole cell homogenate without subcellular fractionation and functional characterization of those proteins altered during I/R injury.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent reports show that a few proteins are altered in humans undergoing liver transplantation. 25,44,45 In addition, some other proteins were also altered in rabbit hearts following I/R injury. 24,46 However, these studies were conducted using whole cell homogenate without subcellular fractionation and functional characterization of those proteins altered during I/R injury.…”
Section: Discussionmentioning
confidence: 98%
“…24,46 However, these studies were conducted using whole cell homogenate without subcellular fractionation and functional characterization of those proteins altered during I/R injury. 25,44,46 In this study, we specifically aimed at identifying the oxidatively-modified target proteins by focusing on redox modulation of Cys residues and evaluating their functional roles in acute hepatic I/R injury, in the presence or absence of a SOD mimetic/peroxynitrite scavenger. The early time point of reperfusion (2-h) was intentionally chosen to identify early signs of oxidative modifications, which may lead to mitochondrial dysfunction prior to a secondary wave of severe liver damage inflicted by infliltrating immune cells during reperfusion for longer times.…”
Section: Discussionmentioning
confidence: 99%
“…Each sample was analyzed in triplicate, and then a comparative analysis was carried out as previously reported (59). Differential spots from two-dimensional electrophoresis (2-DE) were excised from the gel, triturated, and washed with water.…”
Section: Methodsmentioning
confidence: 99%
“…Differential spots from two-dimensional electrophoresis (2-DE) were excised from the gel, triturated, and washed with water. Proteins were in-gel reduced, S alkylated, and digested with trypsin as previously reported (59). Digest aliquots were removed and subjected to a desalting/concentration step on ZipTip C 18 column (Millipore Corp., Bedford, MA) using acetonitrile as the eluent before matrix-assisted laser desorption ionization-time of flight mass spectrometry analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Two proteomic studies revealed that the liver proteome changes during OLT; modifications were found to include upregulation of proteins associated with energy metabolism, various metabolic pathways, oxidative-stress antioxidant response, and lipid metabolism) (17,18). Unfortunately, the design of these studies did not allow to answer the question whether or not these modifications would finally result in elevation of oxidative and nitrosative stress.…”
Section: Discussionmentioning
confidence: 99%